The gallium solar neutrino capture cross section revisited - W.C. Haxton; Evan Rule (Physics Letters B)
Solar neutrino flux constraints from the legacy GALLEX/GNO and SAGE experiments continue to influence contemporary global analyses of neutrino properties. The constraints depend on the neutrino absorption cross sections for various solar sources. Following recent work updating the 51Cr and 37Ar neutrino source cross sections, we reevaluate the 71Ga solar neutrino cross sections, focusing on contributions from transitions to 71Ge excited states, but also revising the ground-state transition to take into account new 71Ge electron-capture lifetime measurements and various theory corrections. The excited-state contributions have been traditionally taken from forward-angle (p,n) cross sections. Here we correct this procedure for the ≈10%–20% tensor operator contribution that alters the relationship between Gamow-Teller and (p,n) transition strengths. Using state-of-the-art nuclear shell-model calculations to evaluate this correction, we find that it lowers the 8B and hep neutrino cross sections. However, the addition of other corrections, including contributions from near-threshold continuum states that radiatively decay, leads to an overall increase in the 8B and hep cross sections of ≈10% relative to the values recommended by Bahcall. Uncertainties are propagated using Monte Carlo simulations.